Female reproductive suppression in an Australian arid zone rodent, the spinifex hopping mouse. (22nd July 2020) - Berris, K. K.; Breed, W. G.; Moseby, K. E.; Carthew, S. M.
Abstract: The spinifex hopping mouse ( Notomys alexis) is an Australian arid zone rodent that undergoes boom and bust population cycles in its natural environment. Most populations studied to date have been sympatric with exotic predators and introduced herbivores, likely affecting their population dynamics. Therefore, it is unclear whether high‐density populations of hopping mice are regulated by purely extrinsic factors or whether intrinsic factors are also at play. We hypothesized that reproductive suppression of female N. alexis may occur in high‐density populations as has been observed in some other rodent species. Reproductive condition of adult female N. alexis was compared between a high‐density population within the Arid Recovery reserve, where exotic predators and introduced herbivores are excluded, and a low‐density population on adjacent pastoral properties (no exclusions). Trap success was 10 times higher inside the reserve than at pastoral sites, and no adult females were observed breeding in the reserve population, despite 26 % of females at pastoral sites recorded breeding. Our results indicate that adult female N. alexis in the high‐density reserve population were reproductively suppressed, but the similar sex ratios in both populations and the high female body mass and body condition in the reserve indicated that this was not due to demographic differences between the two populations or food scarcity. Our study indicates that the 'busts' observed in arid zone rodent populations may be amplified due to the presence of exotic predators and/or grazing by introduced herbivores. We contend that prior to the introduction of exotic predators and introduced herbivores in Australia, the arid zone rodent N. alexis would likely have been more abundant and intrinsic population regulation through female reproductive suppression may have played a larger role in population regulation. Abstract : We present a study that supports the hypothesis that a high population density can result in female reproductive suppression in the Australian arid zone rodent Notomys alexis . Our results also suggest that population 'busts' observed in Australian arid zone rodent populations may be amplified by exotic predators and introduced herbivores. Prior to European settlement, N. alexis may have been more abundant and intrinsic population regulation mechanisms, such as female reproductive suppression, may have played a larger role in the population dynamics of this species.